Optimization of Nutrition Science Learning through Educational Technology at PGRI Adi Buana University Surabaya - Diana Evawati; Susilowati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The field of nutrition science education at Universitas PGRI Adi Buana Surabaya is transforming, leveraging educational technology to enhance learning outcomes. This study delves into the innovative utilization of educational technology in optimizing nutrition science education. By employing an approach that melds technology and pedagogy, this research aims to elevate the professional development of students. By exploring cutting-edge educational technologies, the study underscores the potential of innovative approaches to reshaping the landscape of nutrition science education. This research contributes to the ongoing discourse on effective pedagogical practices and technology integration in academic settings, explicitly focusing on nutrition science education. The findings offer insights into fostering a dynamic learning environment that nurtures professional growth among students in the field of nutrition science. Keywords: Educational Technology, Professional Development, Innovative Approaches